The Salient Stylistic Features of Majeed Amjad - Saima Iram; Faryal Irshad (بازیافت, 2021)
Stylistics is defined as the study of style, Phonetics, Morphology, Syntax and Semantics as tools of criticism, relatively modern sources of discovering hidden meaning and layers of expression. According Nills Erik Enkvist the style of a poet is analyzed through Language he used. He suggests this analysis upon the basis of two aspects of style. (1) Choice between alternative expressions. (2) Derivation from the norm. Majeed Amjad having unique style and poetics must be analyzed on modern parameters of stylistics. Majeed Amjad has his own distinguish style among the urdu poets. He carved out a new style other. He experimented with metrical forms and rhythms. Stylistic analysis of Amjad’s poetry Lenlighteen the individual traits of his style. Stylistics choice of lexical items, phonetics, Morphological choices and grammatical sources shows distinctive features of his poetics and literary style.